“We Will Not Be a Mirror of Evil”: Bydgoszcz’s Independent Music Scene 1982–1989 - Bytner, Jaroslaw (Porównania, 2024)
In the final decade of Communism Poland, independent bands fell victim to the dysfunctional mechanisms of the system, resulting in effective and multifaceted exclusion. Perhaps the most obvious manifestation of this phenomenon was the problem of recording and publishing music. This inability resulted in obscurity, cultural marginalization and ultimately, mainstream historical omission. In this essay on the independent music scene of Bydgoszcz in the years 1982-1989, I undertake this subject through the lens of the oeuvre of the cold wave band Variété and the punk bands Abaddon and Kompania Karna. Along with other incarnations of the Polish underground, bands from Bydgoszcz wrestled with the obstacles and absurdities of the communist reality. They struggled with the feelings of their impotence in the face of state-driven determinism in order to make a permanent mark on Polish musical history. Despite of this and thanks to their powerful, artistically and ideologically inspirational message, they became an integral part of this fascinating historical era.